CAPRISA 018: a phase I/II clinical trial study protocol to assess the safety, acceptability, tolerability and pharmacokinetics of a sustained-release tenofovir alafenamide subdermal implant for HIV prevention in women. Issue 1 (6th January 2022) - Gengiah, Tanuja Narayansamy; Abdool Karim, Quarraisha; Harkoo, Ishana; Mansoor, Leila; Zuma, Nonhlanhla Yende; Radebe, Precious; Samsunder, Natasha; Baxter, Cheryl; Maharaj, B; Baum, Marc M; Moss, John A; Pozzetto, Bruno; et al.
Abstract : Introduction: Young African women bear a disproportionately high risk for HIV acquisition. HIV technologies that empower women to protect themselves are needed. Safe, potent antiretroviral agents such as tenofovir alafenamide (TAF), formulated as long-acting subdermal implants, offer an innovative solution. Methods and analysis: CAPRISA 018 is a phase I/II trial to evaluate the safety, acceptability, tolerability and pharmacokinetics (PKs) of a TAF free base subdermal silicone implant containing 110 mg of TAF with an anticipated 0.25 mg/day release rate. The phase I trial (n=60) will assess the safety of one implant inserted in six participants (Group 1), followed by dose escalation components (Groups 2 and 3) assessing the safety, tolerability and PK of one to four TAF 110 mg implants releasing between 0.25 mg and 1 mg daily in 54 healthy women at low risk for HIV infection. Data from this phase I trial will be used to determine the dosing, implant location and implant replacement interval for the phase II trial. The phase II component (Group 4) will assess extended safety, PK, tolerability and acceptability of the implant in 490 at risk women, randomised in a 1:1 ratio to the TAF implant and placebo tablet or to the placebo implant and an oral pre-exposure prophylaxis tablet. Safety will be assessed by calculating the percentage change in creatinine clearance from baseline at weeks 4, 12, 24, 36, 72, 96 and 120, compared with the percentage change in the control group. Ethics and dissemination: The South African Health Products Regulatory Authority and the University of KwaZulu-Natal's Biomedical Research Ethics Committee have approved the trial. Results will be disseminated through open access peer reviewed publications, conference presentations, public stakeholder engagement and upload of data into the clinical trials registry. Trial registration number: PACTR201809520959443.